LOGISTICS ASPECTS IN THE BUSINESS PROCESS MANAGEMENT SYSTEM OF THE ENTERPRISE - VORONKO-NEVIDNYCHA, Tetiana; LOPATYNSKYI, Roman; BUTSINA, Maryna; CHEREDNICHENKO, Rostyslav (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article analyzes the main components of logistical aspects in the enterprise's business process management system. Considered interpretations of the concept of "logistics". It was established that logistics activity is a tool for achieving enterprise goals in the business process management system. The main tasks of logistics aspects in the work of the enterprise were studied. The main areas of logistics activity are highlighted. It has been proven that the main purpose of logistics activity is to ensure reliable transportation of products, long-term development and obtaining maximum profit from economic activity. The process of formation of logistics activity is substantiated and analyzed, the main theoretical aspects of logistics are outlined. The work also considers modern elements of logistics activities that can be effective for increasing the profit of agricultural enterprises. On the basis of the analysis, the optimal methods of increasing competitiveness and expanding product sales markets are determined.Logistics is a fundamental factor that ensures uninterrupted operation of the enterprise, which forms its ability to adapt to changes in the market and maintain competitiveness. Effective logistics activities allow the enterprise not only to optimize costs and time, but also to ensure a high level of customer satisfaction thanks to timely and high-quality execution of orders. Effective logistics activities allow the enterprise not only to optimize costs and time, but also to ensure a high level of customer satisfaction thanks to timely and high-quality execution of orders. The implementation of innovative approaches in logistics activity enables specialists to successfully solve specific tasks that are quite important for business, these tasks have a measurable result and, in addition, they are practically all feasible and their solution is limited in time. One of the key aspects that involves the implementation of digital technologies for managing logistics processes and includes the use of modern software products, automation of business processes and other technologies to optimize logistics activities is digital logistics.
Keywords: management; logistics; logistics activities; business processes; development; digital logistics